The Equity Impact of the Value-Added Tax in Bangladesh - Hossain, Shahabuddin (Washington, D.C. : International Monetary Fund, 1994)
This paper investigates the income distributional implications of different value-added tax (VAT) schemes in Bangladesh. The results indicate that a revenue-neutral uniform VAT is regressive in its impact on the income of different households. This paper explores an alternative policy package, consisting of a basic rate of VAT with exemptions for certain commodity groups, chosen on the basis of their distributional characteristics. The welfare consequences of the alternative package are found to be superior to those of the uniform VAT.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet